Empowerment Experiences in Women Domestic Workers of Turrialba, Costa Rica - Sojo Mora, Blanca Luz (2020)
This article presents participatory and formative actions developed in two communities in the canton of Turrialba, province of Cartago, for the empowerment of women, based on the Proyecto Empodero de Acción Social de la Universidad de Costa Rica. The objective of this article is to make visible the results obtained from educational experiences in the personal empowerment and general well-being of women domestic workers, older than 18 years and living in rural areas. A questionnaire based on the Escala de Agencia Personal y Empoderamiento (ESAGE) and empowerment variables and indicators was applied, telephone calls were also made. The responses for each category of analysis were analyzed to understand the issues that operate in an underlying way, in contrast to the theory. Among the results obtained: the sample shows that their participation in the lived experiences has contributed to be perceived as safe, capable women, with desires for improvement and with a strengthened self-esteem.